Enabling environment for circular bioeconomy sector in Burkina Faso - Sanfo, S.; Salack, S.; Diarra, K.; Ouédraogo, S.; Kehinde, O. O.; Gebrezgabher, Solomie A. (International Water Management Institute, 2022)
Burkina Faso has a huge opportunity and natural resources to develop circular bioeconomy (CBE) sector. The agricultural sector employs 63% of the employed workforce and contributes to 16% of the Gross Domestic Product. Large production of cereals results in large quantities of agricultural residues. In a country where the industrial sector is still in its infancy, CBE solutions offer significant opportunities for reconfiguring economies, labor and resource use. However, implementing CBE solutions remains at small scale and scaling up faces numerous challenges. This report reviews the enabling environment - drivers, barriers, and opportunities for promoting CBE initiatives in the country and presents conclusions and recommendations.